An Analysis of Symbols in Robert Frost’s Poetry - Julisthree Casilia Gregoriyani (UPT Publikasi dan Penerbitan Universitas San Pedro, 2023)
This study aims to identify the symbols in Robert Frost‘s poetry and analyze the meaning of those symbols. In this study, the author is going to focus on the symbols in Robert Frost‘s poetry. The author limits this analysis to Five of Robert Frost‘s poetry, they are: “Out -Out ”, “Acquainted with the Night”, “Ghost House”, “My November Guest” and ”A Prayer In Spring”. In writing and analyzing the data on this study, the author used the descriptive qualitative. The author used the library research and technique on this study also content analysis to analyze the problem. The author find out and analyze about the symbols that reflected with theoretically and explain the meaning about the symbols in each poetry. Therefore, the result of this study concludes that In Robert Frost‘s selected poems there are symbols, they are light, the sunset, the saw, darkness, rain, the watchman, flowers, bees, bird love, ghosts, raspberries, the toad, the black bats, the whippoorwill, house, rain, tree, sky and earth. Those having meaning that reflected with theoretically